Proceedings of the International Workshop on Medical Ultrasound Tomography: 14.-15. Oct. 2019, Wayne State University, Detroit, Michigan, USA - Böhm, Christian; Hopp, Torsten; Ruiter, Nicole; Duric, Neb (KIT Scientific Publishing, 2021)
Ultrasound Tomography is an emerging technology for medical imaging that is quickly approaching its clinical utility. Research groups around the globe are engaged in research spanning from theory to practical applications. The International Workshop on Medical Ultrasound Tomography 2019 brought together scientists to exchange their knowledge and discuss new ideas and results in order to boost the research in Ultrasound Tomography.